Machinability improvement by workpiece preheating during end milling AISI H13 hardened steel - Mokhtar, Suhaily; Amin, A. K. M. Nurul; Patwari, Md Anayet Ullah; Abdul Razak, Nurhayati (Trans Tech Publications, 2011)
Hardened materials like AISI H13 steel are generally regarded as s difficult to cut materials because of their hardness due to intense of carbon content, which however allows them to be used extensively in the hot working tools, dies and moulds. The challenges in machining steels at their hardened state led the way to many research works in amelioration its machinability. In this paper, preheating technique has been used to improve the machinability of H13 hardened steel for different cutting conditions. An experimental study has been performed to assess the effect of workpiece preheating using induction heating system to enhance the machinability of AISI H13. The preheated machining of AISI H13 for two different cutting conditions with TiAlN coated carbide tool is evaluated by examining tool wear, surface roughness and vibration. The advantages of preheated machining are demonstrated by a much extended tool life and stable cut as lower vibration/chatter amplitudes. The effects of preheating temperature were also investigated on the chip morphology during the end milling of AISI H13 tool steel, which resulted in reduction of chip serration frequency. The preheating temperature was maintained below the phase change temperature of AISI H13. The experimental results show that preheated machining led to appreciable increasing tool life compared to room temperature machining. Abrasive wear, attrition wear and diffusion wear are found to be a very prominent mechanism of tool wear. It has been also observed that preheated machining of the material lead to better surface roughness values as compared to room temperature machining.